Public space, socio-environmental responsibility and citizenship: a case study on a Brazilian borough - REIS,DANIELE P. (2020)
Abstract Some researchers point out the decline in contemporary cities of the use of public spaces, whether free or restricted access. In this sense, the present essay proposes a reflection on a “public sphere of organized presence”, according to Habermas classification, as a rescue of the importance of this space for the exercise of citizenship and social-environmental responsibility. The reflection was based on the results obtained from a study in the district of Riacho Grande, São Bernardo do Campo, São Paulo, Brazil, in which the environmental perception of the participants of the meetings about the region was known by documentary analysis, direct observation and interviews with questionnaires. It was possible to verify that this public space can facilitate a greater integration between the public administrators and citizens, helping even in the defense to the environment.